Evaluation of Analgesic and Central Nervous System Depressant Effects of Holarrhena antidysenterica Stem on Swiss Albino Mice Model (Bangladesh Pharmaceutical Journal, 2018)
Plants are astonishing reservoir of bioactive natural compounds; many of these are able to exhibit outstanding biological activities in animals. Holarrhena antidysenterica is widely used as a traditional medicine. Aim of the present study was to investigate the possible analgesic and central nervous system (CNS) depressant effects of methanol (MHAS), petroleum ether (PHAS), chloroform (CHAS), dichloromethane (DHAS) and aqueous (AHAS) extracts of the H. antidysenterica stem. The analgesic effect was evaluated by acetic acid induced writhing and hot plate methods at 50 and 100 mg/kg dose. The CNS-depressant effect was assessed by using open field, hole cross and head deep tests at 100 and 200 mg/kg dose. All the extracts had exhibited significant (Pb < 0.01, Pa < 0.001) analgesic and CNS depressant effects at dose dependant manner. CHAL showed maximum analgesic and CNS-depressant effect. It had shown 71.34% inhibition of abdominal writhing and 70.39% elongation of paw licking time at 100mg/kg dose. In CNS-depressant study, it exhibited 88.51% inhibition in open field (locomotion), 83.20% inhibition in hole cross (locomotion) and 85.15% inhibition (head deeping) in head deep test at 200mg/kg dose. Among the five extracts CHAL is a potent analgesic and CNSdepressant agent.Bangladesh Pharmaceutical Journal 20(2): 205-212, 2017